SOCIAL SCIENCES AND HISTORY. INTERDISCIPLINARY NOTES (Andamios, Revista de Investigación Social, 2010)
Following Braudel and the Annales School, this article explores and reviews some ideas, their fundamentals, influence, limits and relevance in the possible and necessary dialogue between historiography and other social sciences, particularly, political science. This review employs notions like plural historical time, the consideration of the constructive processes that structures the state and the acknowledgement of different social temporalities. This, to argue —in note form and in constant consideration of the Mexican case— the pertinence and usefulness of interdisciplinary production.
Keywords: Interdisciplinary; history; politics; social sciences; historical time